The Effect of Time and Corrosion Products Formation on Corrosion Rate of Carbon Steel Pipe Under Turbulent Flow Conditions - J. Slaiman, Qasim; O. Hasan, Basim; M. Mahmood, Shiemaa (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The effect of time (or corrosion products formation) on corrosion rates of carbon steel pipe in aerated 0.1N NaClsolution under turbulent flow conditions is investigated. Tests are conducted using electrochemical polarizationtechnique by determining the limiting current density of oxygen reduction in Reynolds number range of 15000 to 110000and temperature range of 30 to 60oC. The effect of corrosion products formation on the friction factor is studied anddiscussed. Corrosion process is analyzed as a mass transfer operation and the mass transfer theory is employed toexpress the corrosion rate. The results are compared with many proposed models particularly those based on theconcept of analogy among momentum, heat, and mass transport. The capability of these models to predict corrosionrates in presence of corrosion products is examined and discussed. It is found that formation of corrosion products withtime decreases the corrosion rate (or mass transfer rate) at low Reynolds number and temperature while it increases thecorrosion rate at high Re and temperature. It increases momentum transport and this increase depends on temperature,Reynolds number, and corrosion rate. Increasing roughness due to the formation of corrosion products causesoverestimation of analogy correlations results by increasing friction factor and decreasing corrosion rate.